Systems Pharmacology Study of the Anti-Liver Injury Mechanism of Citri Reticulatae Pericarpium - Jianxiong Wu; Xietao Ye; Songhong Yang; Huan Yu; Lingyun Zhong; Qianfeng Gong (Frontiers Media S.A., 2021)
Liver diseases are mostly triggered by oxidative stress and inflammation, leading to extracellular matrix overproduction and prone to develop into liver fibrosis, cirrhosis and hepatocellular carcinoma. Liver injury (LI) refers to various pathogenic factors leading to the destruction of stem cells that then affect the liver's normal function, causing a series of symptoms and abnormal liver function indicators. Citri Reticulatae Pericarpium (CRP) is one of the most commonly used traditional Chinese medicines; it contains flavonoids including hesperidin, nobiletin, and tangeretin. CRP has antibacterial, antioxidant, and antitumor effects that reduce cholesterol, prevent atherosclerosis and decrease LI. Here we analyzed the components of CRP and their targets of action in LI treatment and assessed the relationships between them using a systems pharmacology approach. Twenty-five active ingredients against LI were selected based on ultra-performance liquid chromatography-quadrupole/time-of-flight mass spectrometry results and databases. The drug targets and disease-related targets were predicted. The 117 common targets were used to construct a protein-protein interaction network. We identified 1719 gene ontology items in LI treatment, including 1,525 biological processes, 55 cellular components, and 139 molecular functions. These correlated with 49 Kyoto Encyclopedia of Genes and Genomes pathways. These findings suggest that CRP may counteract LI by affecting apoptotic, inflammatory, and energy metabolism modules. In vitro experiments suggested that the mechanism may involve hesperidin and naringenin acting on CASP3, BAX, and BCL2 to affect the apoptosis pathway, attenuating liver fibrosis. Naringenin significantly inhibited AKT1 phosphorylation, which in turn mediated activation of the phosphoinositide 3-kinase-Akt signaling pathways against LI. This study provides a reference for systematically exploring the mechanism of CRP's anti-LI action and is also expands of the application of systems pharmacology in the study of traditional Chinese medicine.